Evaluation of Development Planning in Riau Islands Province - Desi Waryanti (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The purpose of this research is to analyze the development planning process in the Riau Islands in 2020 which is not optimal. The development planning process is analyzed and described using three indicators by Willian N. Dunn's development planning evaluation theory, that is: (1) efficiency; (2) equality and (3) responsiveness. The research method used is a qualitative research method. The results of this research indicate that although the development planning process starting from the phasing and scheduling carried out by the Riau Islands Provincial Government in the preparation of the 2020 Regional Government Work Plan has been appropriate and stakeholder participation in the Musrenbang is also quite good, the work achievements contained in the regional head performance agreement at the end of the year it was found that 25% of the performance targets had not been achieved.